A clinical study of adhd symptoms with relation to symptoms of learning disorders in schoolchildren in Bogota, Colombia (2012)
Objective: To investigate possible relationships between symptoms of ADHD and of learning disorder (LD) in a population geographically, culturally, and linguistically distinct from previous studies. Method: The authors evaluated a cross section of 834 Colombian schoolchildren for childhood neurological pathologies on the basis of a medical examination and performance with reference to the Diagnostic and Statistical Manual (4th ed.) attention checklist, the General and Differential Aptitudes Battery, and the Visual-Motor Integration (VMI) test. Results: Of the total sample, 382 were classified as 'ADHD only,' 54 as 'LD only,' and 75 as 'ADHD + LD.' A total of 459 had low VMI scores. ADHD, LD, and low VMI were significantly interrelated. Among the children with ADHD, the attention deficit subtype tended to have more learning problems than the hyperactive subtype, who showed no major deficiencies in their learning ability. Conclusions: This study provides additional evidence demonstrating a relationship between LD and ADHD, particularly with respect to verbal reasoning, visual-auditory memory, and VMI. © 2012 SAGE Publications.